2022
DOI: 10.3233/jad-220377
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve Modulates Brain Structure and Cortical Architecture in the Alzheimer’s Disease

Abstract: Background: Cognitive reserve (CR) explains the individual resilience to neurodegeneration. Objective: The present study investigated the effect of CR in modulating brain cortical architecture. Methods: 278 individuals [110 Alzheimer’s disease (AD), 104 amnestic mild cognitive impairment (aMCI) due to AD, 64 healthy subjects (HS)] underwent a neuropsychological evaluation and 3T-MRI. Cortical thickness (CTh) and fractal dimension (FD) were assessed. Years of formal education were used as an index of CR by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…The copyright holder for this preprint this version posted September 9, 2022. ; https://doi.org/10.1101/2022.09.08.22279748 doi: medRxiv preprint the left prefrontal lobe, and increased fractional dimension in the right temporal and in the left temporo-parietal lobes compared to those with lower reserve [43]. Future studies combining the spatial accuracy of MRI and the temporal dynamics of EEG may elucidate the mediating effects of cognitive reserve between localized brain compensatory activity and neural efficiency across the cognitive aging spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted September 9, 2022. ; https://doi.org/10.1101/2022.09.08.22279748 doi: medRxiv preprint the left prefrontal lobe, and increased fractional dimension in the right temporal and in the left temporo-parietal lobes compared to those with lower reserve [43]. Future studies combining the spatial accuracy of MRI and the temporal dynamics of EEG may elucidate the mediating effects of cognitive reserve between localized brain compensatory activity and neural efficiency across the cognitive aging spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rectified area P3 amplitudes in the central and frontal channels compared to the parietal channels support this hypothesis. However, the time window for modulation of cognitive reserve on brain reserve may be limited to individuals with MCI [43]. Higher cognitive reserve in older adults with amnestic MCI was associated with lower macromolecular tissue volume across major white tracts, whereas no such relationship was observed in individuals with AD [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 A structural MRI study reported that lower grey matter volumes in presymptomatic carriers of genetic mutations for frontotemporal dementia (FTD) were influenced by both genetic factors and CR proxies, including educational attainments. 83,84 Another study utilized voxel-based morphometry to measure regional gray matter volume at a voxel scale in MRI to evaluate the effect of formal education on the brain tissue of patients with aMCI or fully developed AD. The groups were divided into high and low levels of formal education.…”
Section: Sociobehavioral and Neuropsychological Proxies Of Crmentioning
confidence: 99%
“…Neuroimaging researches have indicated that CR is linked to enhanced connectivity within cognitive control networks, particularly between the left frontal cortex and the dorsal attentional network in MCI ( Franzmeier et al, 2017a , b ). Additionally, it has been demonstrated that CR could modify cortical architecture and WM macromolecular volume, enhance cerebral blood flow, which may alleviate cognitive decline in MCI ( Fingerhut et al, 2022 ; Serra et al, 2022 ; Brenner et al, 2023 ; Zhou et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%